2020
DOI: 10.1128/jcm.00057-20
|View full text |Cite
|
Sign up to set email alerts
|

Direct Blood Culturing of Candida spp. on Solid Medium by a Rapid Enrichment Method with Magnetic Beads Coated with Recombinant Human Mannan-Binding Lectin

Abstract: A rapid and accurate method to identify the species and antibiotic resistance of Candida spp. in blood is vital to increase the survival rates of patients with bloodstream infections. However, the extremely low levels of Candida spp. in blood make rapid diagnosis by standard blood culture difficult. In this study, we constructed a direct blood culturing method (i.e., the M1 method) by a rapid enrichment method with magnetic beads coated with a recombined human mannan-binding lectin (rhMBL; i.e., M1 protein), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Compared with the traditional culture method, it has been shown that after enrichment with magnetic beads, bacteria can be detected several hours or even several days earlier. In contrast to most studies, we did not use specific antibodies to capture a specific pathogen but instead used M1 protein to non-specifically capture pathogens with an M1 protein binding site from the blood (Chen et al 2020 ). In addition, in the subsequent nucleic acid amplification stage, we used a rapid RAA isothermal amplification assay.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared with the traditional culture method, it has been shown that after enrichment with magnetic beads, bacteria can be detected several hours or even several days earlier. In contrast to most studies, we did not use specific antibodies to capture a specific pathogen but instead used M1 protein to non-specifically capture pathogens with an M1 protein binding site from the blood (Chen et al 2020 ). In addition, in the subsequent nucleic acid amplification stage, we used a rapid RAA isothermal amplification assay.…”
Section: Discussionmentioning
confidence: 99%
“…The M1 protein was supplied by the Nosocomial Infection Laboratory of the National Institute for Communicable Disease Control Prevention, Chinese Center for Disease Control and Prevention (Chen et al 2020 ). The protein concentration was determined and frozen at −80℃.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…During his hospitalization, three standard blood cultures with BacT/ALERT3D60 system (bioMé rieux, France) were all negative. Direct culture with M1 beads enrichment was performed as described previously (1). Small colonies were grown on agar plate.…”
Section: Casementioning
confidence: 99%